Economic security system in the field of IT technologies at Tinkoff Bank - M. A. Dotsenko (Путеводитель предпринимателя, 2020)
Currently, automation of processes in companies is a necessary process, as it improves their activities. The automation tool is the introduction and use of information technologies. The author examines the system of economic security in the field of IT technologies in Tinkoff Bank.